(untitled) (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
This study aims to identify the reproductive challenges encountered through the women of differing abilities. Especially, what are the specific reproductive challenges encountered by women of differing abilities? How do societal attitudes and perceptions impact the reproductive health with differing abilities? What are the barriers to accessing reproductive healthcare services for women with disabilities? are the major questions which have been addressed and fulfilling through the following specific objectives such as to identify the specific reproductive challenges encountered by women with differing abilities, to analyze the impact of societal attitudes, and perceptions on the reproductive health with differing abilities and to assess the barriers that hinder access to reproductive healthcare services for women with disabilities. In this study researcher has employed a cross-sectional research design and adopted a quantitative methodology. Likewise, this study is based within Kirtipur Municipality, Kathmandu, Nepal. The study focused on women who had disabilities and registered in Kirtipur Municipality. Since the exact population for the study was unknown, a two-stage sampling approach was used. In the first stage, a list of women with disabilities registered in Kirtipur Municipality was purposively selected. In the second stage, 40 respondents, constituting 35.40% of the total list of 113 respondents, were randomly chosen using a simple random sampling method. Data collection primarily relied on the use of a questionnaire. Both structured and unstructured questionnaire formats were designed to gather quantitative information from the intended respondents.